Transportborrning : Undersökningsborrning i Kiirunavaara - Svahn, Amanda (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2019)
In the Kiirunavaara mine, the total length of drilling is about 1138000 meters each year with two different drilling methods. Production drilling is performed with a hammer drill while explorationdrilling is performed with a diamond drill. Explorationdrilling is applied toidentify the position ofthe ore and its tonnage. In the diamond drilling method different core samples aretaken out to provideinformation about the geological structure andwall rock in order to plan for theinfrastructure. For that reason,it isimportant that the exploration drilling isalways ahead of the production. All drill coresareexamined and stored. When a drill core isup to 1000 meters long a great amount of information needs to becompiled. The present report describestransport drilling,which impliesthat the first100 meters of each drilling will be completed with the hammer drillingmethod. The hammer drilling can be used to drill about 100 meters each day compared to coredrilling that would take almost aweek. Forthe moment there is 420 drill holes planned in Kiruna mine with a total length of 190000 drill meters. By applying transport drilling and use the hammer drilling method at the first 100 meters for eachdrill hole canthese42000 meters be drilled in 420 days,instead of 356 weeks with the core drilling method. Hammer drilling is efficient in terms of time compared to diamond drilling but does not provide the same information about the rock. Inorder to applaythe method of hammer drilling in transport drilling, different methods need to be tested that can provide information which isnecessary for mining.This report summarizes different methods that can complete a core. Amongst others, optical logging can be used wherea camera is used to film the walls inside the drill holes. In addition, samples of drill cuttingscan be collected fromhammer drillingforanalysisof the material.The report also contains information about oriented drilling. Here,an instrument is mounted on the core drill equipment. Oriented drilling does not affect the hammer ...